Storytelling in Media Communication: Media and Art Models - Amangeldiyeva, Gulmira S.; Toktagazin, Muratbek B.; Omarov, Bauyrzhan Zh.; Tapanova, Saule S.; Nurtazina, Roza A. (International Journal of Criminology and Sociology, 2022)
The article is devoted to study of storytelling models in media communication in the context of globalization and postmodernism of information space. This article is of interest because recently storytelling as a special type of communication has become an object of research in science. Advertising has modified, turning into art of storytelling and brand-image. In this article, the specifics of storytelling are analysed, its definition is provided, functions and types are pointed out. The authors also consider such phenomena as landing and longread inseparable from storytelling in online space. In the article, there is characteristic of each component of technique of transmedia narration in the context of postmodernism information community and globalisation changes. The author analyses how the story in advertising is tool of reflection and experience transfer, value and cultural identification and how affect the audience. Using the example of popular commercials, the author studies how storytelling and myth are connected and how it is implemented within media space.